Let the Voters Choose Women - Audinga Baltrunaite; Alessandra Casarico; Paola Profeta; Giulia Savio (Center for Economic Studies and ifo Institute (CESifo), 2016)
Female under-representation in politics can be the result of parties' selection of candidates and/or of voters' electoral preferences. To assess the impact of these two channels, we exploit the introduction of Italian Law 215/2013, which prescribes both gender quotas on candidate lists and double preference voting conditioned on gender. Using a Regression Discontinuity Design, we estimate that the law increases the share of elected female politicians by 22 percentage points. The result is driven by the increase in preference votes cast for female candidates, suggesting a salient role of double preference voting in promoting female empowerment in politics.
Keywords: D72; J45; 330; gender quotas; municipal elections; regression discontinuity design